Process evaluation of five tailored programs to improve the implementation of evidence-based recommendations for chronic conditions in primary care - Straßner, Cornelia; Freund, Tobias; Szecsenyi, Joachim; Wensing, Michel (Implementation science, 2016)
Although there is evidence that tailored implementation strategies can be effective, there is little evidence on which methods of tailoring improve the effect. We designed and evaluated five tailored programs (TPs) each consisting of various strategies. The aim of this study was to examine (a) how determinants of practice prioritized in the design phase of the TPs were perceived by health care professionals who had been exposed to the TPs and whether they suggested other important determinants of practice and (b) how professionals used the offered strategies and whether they suggested other strategies that might have been more effective.